Science World (Videorecording) Ecology : Lakes and Streams; Deciduous Forest. - Coronet (Northbrook, IL Copronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.
Vol. 12: Lakes and Streams; Deciduous Forest
With DVD copy (CD-001294)
[Distributed by] International Book International, Philippines
Keywords: Lakes; Streams; Deciduous Forest